Republic of Lithuania : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues paper examines the reasons behind Lithuania's low tax-GDP ratio relative to the European Union (EU). At end-2015, Lithuania had nearly the lowest tax-GDP ratio in the EU, along with Bulgaria and Romania. The tax revenue shortfall relative to the EU is for the most part attributable to weak tax administration and tax policy, with the structure of the economy playing a secondary role. The second largest contribution to the tax revenue shortfall relative to the EU comes from social security contributions. The shortfall is driven primarily by the structure of the economy, and to a smaller extent by tax administration.